Global Attractors for Abstract Evolutionary Equations - Aris, Naimah (Jurnal Matematika, Statistika dan Komputasi, 2018)
We establish in this paper that under usual assumption on the function in abstract Cauchy problem, the existence of global attractor for the semigroup generated in this problem is merely a consequence of such a priori estimate. It is shown that asymptotic behavior of solutions can controlled by this estimate.